2019
DOI: 10.1038/s41467-019-12237-y
|View full text |Cite
|
Sign up to set email alerts
|

Tunable assembly of truncated nanocubes by evaporation-driven poor-solvent enrichment

Abstract: Self-assembly of nanocrystals is extensively used to generate superlattices with long-range translational order and atomic crystallographic orientation, i.e. mesocrystals, with emergent mesoscale properties, but the predictability and tunability of the assembly methods are poorly understood. Here, we report how mesocrystals produced by poor-solvent enrichment can be tuned by solvent composition, initial nanocrystal concentration, poor-solvent enrichment rate, and excess surfactant. The crystallographic coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…It is important to mention that these supracrystals fall apart into separate units (mesocrystals) when immersed in water and ultrasonicated for a few minutes. This indicates that while drying, adsorbed water molecules leave the surface of the particles, leading to the changes of the surface properties [52, 53] . Capillary forces guide the formation of the supracrystals but no strong bonding is formed between individual mesocrystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that these supracrystals fall apart into separate units (mesocrystals) when immersed in water and ultrasonicated for a few minutes. This indicates that while drying, adsorbed water molecules leave the surface of the particles, leading to the changes of the surface properties [52, 53] . Capillary forces guide the formation of the supracrystals but no strong bonding is formed between individual mesocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that while drying, adsorbed water molecules leave the surface of the particles,leading to the changes of the surface properties. [52,53] Capillary forces guide the formation of the supracrystals but no strong bonding is formed between individual mesocrystals.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that free OA in the dispersions with added OA (GP48) increased the inter-particle spacing and promoted the growth of large superlattices, which corresponds well to previous studies that concluded that the addition of free OA is required to form large and well-ordered Small 2022, 18, 2106768 superlattices from oleate-capped nanoparticles by evaporationdriven self-assembly. [29,37] No structural transformation could be deduced from the SAXS data during t = 245 to 600 s of the second stage of solvent removal when the medium is dominated by 1-pentanol (Figure 4c) and the polarity remained unchanged at ε = 13.7 (Figure 4d). Although no lattice transformation occurred during the lattice expansion, the displacement increased dramatically from 2.65 nm to 3.33 nm and the characteristic length slightly decreased from 113 nm to 91 nm (Figure S2d, Supporting Information).…”
Section: Sample Id Timementioning
confidence: 99%
“…Lv et al used a multi-method approach to investigate the superlattice formation by poor-solvent enrichment, modifying solvent composition, initial nanocrystal concentration, poor-solvent enrichment rate, and excess surfactants. [275] In situ SAXS experiments were performed using different solvent modification on evaporating droplets, as introduced in the previous subsection. It was found that a higher crystalline quality of superlattices is achieved with a sufficient addition of excess oleic acid as surfactant which resulted in large and well-ordered supercrystals.…”
Section: Changing Solvent Propertiesmentioning
confidence: 99%